Mullerian Adenosarcoma of the Uterus with Sarcomatous Overgrowth - Singh, Reecha (Libertas Academica, 2010)
BACKGROUND AND OBJECTIVES: Mullerian adenosarcoma is an uncommon variant of mixed mesodermal tumour of the uterus. This is a case report of a 65 year old post-menopausal lady who presented with complaints of passing tissue fragments per vaginum for 2 days followed by spotting. On examination, a polypoid mass protruding through the cervix was seen which was biopsied. Following a preliminary histologic diagnosis of poorly differentiated sarcoma on the biopsy; the patient underwent total abdominal hysterectomy with bilateral salpingo-oopherectomy. METHOD: The surgical specimen was formalin fixed and paraffin embedded. Haematoxylin and eosin stained sections were studied. RESULT AND CONCLUSION: Histopathological examination of the polypoid mass revealed a tumour comprising of an admixture of benign endometrial glandular component with overgrowth of sarcomatous stromal component and heterologous elements. This may pose a problem in diagnosis due to its rarity, and hence its distinctive morphological features merit attention as described here. In view of the rarity of this tumor, it is mandatory to do extensive histologic sampling to identify areas of sarcomatous overgrowth before arriving at a diagnosis of mullerian adenosarcoma as the clinical course and management vary.